SOSIALISASI PERLINDUNGAN MEREK DAN HAK KEKAYAAN INTELEKTUAL BAGI PELAKU UMKM DI KECAMATAN DUMBO RAYA, KOTA GORONTALO - Karlin Z. Mamu; Melki T. Tunggati; Nirwan Junus; Sri Olawaty DJ. Suaib (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aims to enhance the legal understanding and awareness of Micro, Small, and Medium Enterprises (MSMEs) in Dumbo Raya Subdistrict, Gorontalo City, regarding the importance of trademark protection and intellectual property rights (IPR) under Law No. 20 of 2016 on Trademarks and Geographical Indications. The method employed was a participatory educational approach through legal outreach sessions, seminars, interactive discussions, and evaluations based on pre-test and post-test questionnaires. The results of the activity showed that prior to the outreach, the majority of participants had very low levels of legal literacy, both in terms of conceptual understanding of trademarks and technical understanding of the trademark registration process at the Directorate General of Intellectual Property. After the outreach activities were conducted, there was a significant improvement in all aspects of the participants’ legal understanding and awareness. These findings demonstrate that structured and practical legal outreach is an effective tool for promoting IPR literacy and fostering sustained legal compliance among MSME operators.